Supporting Mobile Application Development with Model-Driven Emulation - Bowen, Judy; Hinze, Annika (Electronic Communications of the EASST, 2011)
In this paper we outline our proposed approach for supporting mobile application development by using models as inputs to an emulator. We describe a new user interface to a parser tool previously developed, which enables developers to make design decisions about the user interface of the mobile application whilst ensuring that the resulting application adheres to the models. This paper describes work currently in progress.